2020
DOI: 10.3906/bot-1912-23
|View full text |Cite
|
Sign up to set email alerts
|

Relation between soil salinity and species composition of halophytic plant communities: A baseline data inventory for wetland monitoring

Abstract: Our study sets forth the outcomes of an interdisciplinary project conducted in order to fill the information gap on the management of a wetland ecosystem, in the case of a protected area on the southeastern coast of Turkey. The hypothesis of the study is that the pattern of species composition reflects soil salinity level and some species can act as relevant indicators. The study aimed to discover a relationship between soil salinity and vegetation composition and establish some indicators useful for monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Accordingly, some authors demonstrated a greater salt tolerance in the germination phase for annual plants than in perennials and explained it in terms of their pioneer character, differences in the habitat colonized and the ability to complete the life cycles rapidly in an unpredictable environment [82]. In contrast, other authors identified annuals as the most sensitive to salinity [1], with stress escaping strategies [83,84]. Our results are in accordance with latter findings as they show a higher tolerance in the perennial H. perfoliata than in the annual H. amplexicaulis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, some authors demonstrated a greater salt tolerance in the germination phase for annual plants than in perennials and explained it in terms of their pioneer character, differences in the habitat colonized and the ability to complete the life cycles rapidly in an unpredictable environment [82]. In contrast, other authors identified annuals as the most sensitive to salinity [1], with stress escaping strategies [83,84]. Our results are in accordance with latter findings as they show a higher tolerance in the perennial H. perfoliata than in the annual H. amplexicaulis.…”
Section: Discussionmentioning
confidence: 99%
“…Salt-affected habitats are complex environments in which subtle changes in ecological factors determine plant occurrence, communities' richness and distribution [1]. In this sense, differences in levels of germination success linked to salt tolerance and biotic interactions during seedling emergence and establishment are important in plant composition and salt marsh zonation patterns [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation